Impact of aging on immunity in the context of COVID-19, HIV, and tuberculosis - Grifoni, Alba; Alonzi, Tonino; Alter, Galit; Noonan, Douglas McClain; Landay, Alan L.; Albini, Adriana; Goletti, Delia (Frontiers in Immunology, 2023)
Knowledge of aging biology needs to be expanded due to the continuously growing number of elderly people worldwide. Aging induces changes that affect all systems of the body. The risk of cardiovascular diseases and cancer increase with age. In particular, the age-induced adaptation of the immune system causes a greater susceptibility to infections and contributes to the inability to control the pathogen growth and to immune-mediated tissue damage. Although the impact of aging on immune functions is far to be elucidated, this review addresses some of the recent understanding of age-related changes affecting key components of immunity, with particular emphasis on immune-senescence during the most common infectious disease worldwide still characterized by a high mortality, such as COVID-19, HIV infection and tuberculosis.